Analisis Pengelolaan Biaya Produksi di PT Indofood Sukses Makmur TBK Deli Serdang - Simamora, Enjelika; Hombing, Eva Ulina Br; Simanjuntak, Mery Kristiani; Fitrahwaty, Fitrahwaty; Ruslan, Dede (Journal of Management Accounting, Tax and Production, 2025)
The food industry is a very vital sector in the Indonesian economy. With a large population and increasing food consumption needs, food and beverage companies, such as PT Indofood Sukses Makmur Tbk, have a crucial role in providing quality food products to the community. PT Indofood Sukses Makmur Tbk, especially the branch in Deli Serdang, North Sumatra, is one of the largest food producers in Indonesia. Indofood Sukses Makmur TBK is one of the giant companies in Indonesia which operates in the food processing sector. Founded in 1990, this company has evolved into a major leader in food product categories, such as instant noodles, seasonings, drinks and other processed products. The objectives of this research are 1) to find out the method of implementing production costs at PT Indofood Sukses Makmur TBK Deli Serdang, 2) to increase understanding of one of the food industries in Indonesia. The research results show that the cost of packaging materials, especially labels and cardboard, has the largest contribution to total production costs. The composition of packaging material costs of IDR 800,067,857,000 (44.7%) indicates the importance of more efficient management of packaging material costs. The overall analysis results show that with more efficient management costs, PT Indofood Sukses Makmur Tbk can reduce total production costs and increase competitiveness in the food industry.